Optimizing weight loss for athletes - Walberg Rankin, J. (2000)
* Most active people must focus on dietary change to lose weight because they already have high rates of energy expenditure. * To reduce risk of adverse health and performance consequences, the rate of weight loss should not exceed 1-2 % of body weight per week. * Body weight goals for athletes should be based on: current body composition, time remaining until the competitive season, body weight history, and sport-specific rules. * Diet recommendations for weight loss include modest energy restriction (-500 to750 kcal/d), low fat (20-25% of energy intake), moderate protein (15-25% of energy but not greater than 2 g/kg body weight per day), and high carbohydrate (60-70% of energy). * Avoid reliance on supplements and fad diets.